ChemInform Abstract: Abrupt Symmetry Decrease in the ThT2Al20 Alloys (T = 3d Transition Metal). Issue 45 (November 2015) - Uziel, A.; Bram, A. I.; Venkert, A.; Kiv, A. E.; Fuks, D.; Meshi, L.
Abstract ThM2Al20 (M: Ti, V, Mn, Fe) alloys are prepared by arc melting of the elements followed by annealing (Ta foil in quartz capsule under Ar, 800 °C, 3 weeks).